2014
DOI: 10.2503/jjshs1.ch-054
|View full text |Cite
|
Sign up to set email alerts
|

Expression Quantitative Trait Loci Analysis of Carotenoid Metabolism-related Genes in Citrus

Abstract: The expression profiles of carotenoid metabolism pathway genes are one of the important factors that regulate carotenoid content and composition in the fruit of Citrus cultivars. To identify regulatory factors of gene expressions in the carotenoid pathway, expression quantitative trait loci (eQTL) analysis was applied using a hybrid population. In the analyzed population, significant eQTLs for phytoene synthase (PSY), phytoene desaturase (PDS), z-carotene desaturase (ZDS), b-ring hydroxylase (HYb), and zeaxant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Therefore, in order to determine candidate genes related to targeted traits, transcript abundances had been used as quantitative trait data in the QTL analysis (Druka et al, 2010; Galpaz et al, 2018; García-Gómez et al, 2019). Multiple authors have noted the usefulness of gene expression analysis based on qPCR for the experimental validation of QTLs in fruit crops (Huang et al, 2014; Sugiyama et al, 2014; García-Gómez et al, 2019), confirming the correlation between genotype and gene expression levels (Conesa et al, 2016).…”
Section: Introductionmentioning
confidence: 74%
“…Therefore, in order to determine candidate genes related to targeted traits, transcript abundances had been used as quantitative trait data in the QTL analysis (Druka et al, 2010; Galpaz et al, 2018; García-Gómez et al, 2019). Multiple authors have noted the usefulness of gene expression analysis based on qPCR for the experimental validation of QTLs in fruit crops (Huang et al, 2014; Sugiyama et al, 2014; García-Gómez et al, 2019), confirming the correlation between genotype and gene expression levels (Conesa et al, 2016).…”
Section: Introductionmentioning
confidence: 74%
“…Comparing the eQTL obtained based on the relative expression data of the target genes and the QTL of the starch quantification in the inoculated group and CLas quantification (Ct values), it was expected that some eQTL would contribute to the phenotypes. This was evidenced by the finding of overlaps between eQTL and QTL, indicating the existence of complex regulatory networks for both gene expression and phenotype (Sugiyama et al 2014;Lima et al 2018). It was observed that the positions in cM from the beginning of the overlapping eQTL/QTL were fairly close, with some exceptions showing a relatively large distance; QTL usually cover large regions of the genome (at least 20 cM) (Gion et al 2000;Brown et al 2003;Lima et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The co-localization of eQTL and QTL represents the association between the allelic state of genomic regions with the quantification of gene transcripts within QTL involved in the variation of phenotypic characteristics (Sugiyama et al 2014;Lima et al 2018). With the exception of the T6PP and BAC2 genes, all of the genes presented eQTL co-located with QTL, independent of the map and the phenotypic characteristics (CLas or starch quantification).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various QTLs for other carotenoid components were also detected, but most of them expressed low LOD values. Sugiyama et al (2014) extended the study to compare the genetic locus and expression QTL (eQTL) of carotenoid metabolic genes using AG population. Firstly, genetic loci of the major carotenoid metabolic genes were mapped as follows: PSY on linkage group (LG)-4, PDS on LG-3, ZDS on LG-9, CHYB on LG-3, and ZEP on LG-2.…”
Section: ) Transcriptional Regulation Of Citrus Carotenoid Biosynthementioning
confidence: 99%